Peptide Allergen Immunotherapy: A New Perspective in Olive-Pollen Allergy - David Calzada; Lucía Cremades-Jimeno; María López-Ramos; Blanca Cárdaba (MDPI AG, 2021)
Allergic diseases are highly prevalent disorders, mainly in industrialized countries where they constitute a high global health problem. Allergy is defined as an immune response "shifted toward a type 2 inflammation" induced by the interaction between the antigen (allergen) and IgE antibodies bound to mast cells and basophils that induce the release of inflammatory mediators that cause the clinical symptoms. Currently, allergen-specific immunotherapy (AIT) is the only treatment able to change the course of these diseases, modifying the type 2 inflammatory response by an allergenic tolerance, where the implication of T regulatory (Treg) cells is considered essential. The pollen of the olive tree is one of the most prevalent causes of respiratory allergic diseases in Mediterranean countries, inducing mainly nasal and conjunctival symptoms, although, in areas with a high antigenic load, olive-tree pollen may cause asthma exacerbation. Classically, olive-pollen allergy treatment has been based on specific immunotherapy using whole-olive pollen extracts. Despite extracts standardization, the effectiveness of this strategy varies widely, therefore there is a need for more effective AIT approaches. One of the most attractive is the use of synthetic peptides representing the B- or T-cell epitopes of the main allergens. This review summarizes experimental evidence of several T-cell epitopes derived from the Ole e 1 sequence to modulate the response to olive pollen in vitro, associated with several possible mechanisms that these peptides could be inducing, showing their usefulness as a safe preventive tool for these complex diseases.